Risk Analysis of Work Accidents in the Loading and Unloading Process Using Job Safety Analysis (JSA) and Hazard and Operability Study (HAZOPS) Methods at PT Pelindo II (Persero) Branch Pontianak: Analisis Risiko Kecelakaan Kerja pada Proses Bongkar Muat Menggunakan Metode Analisis Keselamatan Kerja (JSA) dan Studi Bahaya dan Kemampuan Operasi (HAZOPS) di PT Pelindo II (Persero) Cabang Pontianak - Sri Puji lestari; Selviana; Linda Suwarni (Indonesian Journal of Administration and Health Research (IJAHR), 2024)
Loading and unloading companies are at high risk for work accidents. This study aims to identify, assess, and control health and safety risks in the loading and unloading process at PT Pelindo II (Persero) Branch Pontianak in 2021, using the JSA, HAZOPs, and AS/NZS 4360:2004 methods with 60 respondents. The loading and unloading process consists of three sections: Receiving/Delivery, Haulage/Trucking, and Stevedoring, with mechanical hazards being dominant (75%) in Haulage/Trucking and Stevedoring. The risk assessment shows that several work stages have high risks that need to be controlled, while others are acceptable with control. Recommendations include strengthening SOP compliance, using PPE, implementing administrative and engineering controls, as well as periodic training and safety talks to improve work safety awareness. Keyword: Risk Analysis, Job Safety Analysis (JSA), Hazard and Operability Study (HAZOPS), Loading and UnloadingPerusahaan bongkar muat berisiko tinggi terhadap kecelakaan kerja. Penelitian ini bertujuan mengidentifikasi, menilai, dan mengendalikan risiko kesehatan dan keselamatan kerja pada proses bongkar muat di PT Pelindo II (Persero) Cabang Pontianak Tahun 2021, menggunakan metode JSA, HAZOPs, dan AS/NZS 4360:2004 dengan 60 responden. Proses bongkar muat terdiri dari tiga bagian: Receiving/Delivery, Haulage/Trucking, dan Stevedoring, dengan bahaya mekanik dominan (75%) pada Haulage/Trucking dan Stevedoring. Penilaian risiko menunjukkan beberapa tahapan kerja memiliki risiko tinggi yang perlu dikendalikan, sementara tahapan lainnya dapat diterima dengan pengendalian. Rekomendasi meliputi penguatan kepatuhan SOP, penggunaan APD, pengendalian administrasi dan rekayasa teknik, serta pelatihan dan safety talk berkala untuk meningkatkan kesadaran keselamatan kerja. Kata Kunci: Analisis Risiko, Job Safety Analysi (JSA), Hazard and Operability Study (HAZOPS), Bongkar Muat